Trajectory-based analysis on pedestrian turning movement on a stair landing. (March 2022) - Ye, Rui; Fang, Zhiming; Huang, Zhongyi; Lian, Liping; Li, Xiaolian; Gao, Yan; Liu, Jiajia
Highlights: An experiment on pedestrian turning movement on the stair landing is conducted. Pedestrian descent and ascent behaviors on the stair landing are compared. Two phases can be found based on pedestrian speed on the stair landing. Two regimes can be spotted for fundamental diagrams on the stair landing. Empirical values for parameters in the method based on hypothetical travel path are provided. Abstract: In this paper, we conduct a trajectory-based analysis on pedestrian turning movement on a stair landing. The extracted trajectories indicate pedestrians walk along arc paths. The compression effect resulting from pedestrians' desire to seek the shortest path during the turning movement is not observed. Based on the developing trends of angular speed and speed, two phases can be distinguished during the whole turning process, namely deceleration and uniform speed phase when moving downstairs, and acceleration and uniform speed phase when moving upstairs. According to the fundamental diagrams, compared with ascent movement, pedestrians move faster when going downstairs on the stair landing, and the speed is much lower than that in the straight corridor, due to the effect of turning movement and stairs. Two regimes can be spotted from the fundamental diagrams. When the density is lower than the critical one, the speed decreases sharply with the increase of density, while it decreases smoothly when the density is higher than the critical one. According to the density distributions, the area with the maximal density occurs after turning for descent movement, while it occurs before turning for ascent movement. Taking the average speed computed from trajectories as a reference, we further provide some empirical values for parameters (e.g., the turning radius of the arc path) proposed in the method based on hypothetical travel path.